An Analysis of Electronic Services Quality in Intellectual Property Using Gap Analysis and Importance Performance Analysis (IPA) as Public Service Quality Improvements - Junaidi Abdillah (Badan Strategi Kebijakan Hukum, 2022)
This study measures the quality of Intellectual Property (IP) service accessed through websites (e-services) as the main characteristics of services. It is conducted by reviewing the expected service and the perceived service of service users. The research used an instrument adapted from the E-GovQual model and which was modified according to the characteristics of IP e-services. The calculations and analysis of this study was carried out using gap analysis and importance performance analysis (IPA) techniques on 404 user ratings through online surveys. The results of this research show that the quality of IP e-services implementation has not fully met the needs and expectations of users (96% conformity level or 100%). The main cause of gap in the quality of IP e-services today is caused by gap in the dimensions of support for the public (citizens support; gap score -0.29) and efficiency (efficiency; gap score -0.26). In terms of the IP service standard policy, several important components have not been fully and clearly regulated, both in the delivery process and in the management of services organized electronically. As a priority aspect, building public trust and confidence need to be improved. The supports to the users through information, interaction and transactions are needed to be optimized. Improving service standard policy is a strategy that DGIP needs to consider in meeting the current needs for a better quality of IP e-service.